Carbon Flow for Plankton Metabolism of Saco do Mamanguá Ría, Bay of Ilha Grande, a Subtropical Coastal Environment in the South Brazil Bight - Brandini, Frederico; Michelazzo, Luan Sayeg; Freitas, Gabriel Ruske; Campos, Giulia; Chuqui, Mateus; Jovane, Luigi (Frontiers in Marine Science, 2019)
The autotrophic plankton assemblage along the subtropical coastal embayments of the South Brazil Bight is dominated by the cyanobacteria Synechococcus. This investigation evaluated the contribution of photosynthetic carbon fixation to the total Carbon metabolism within the planktonic system of Mamanguá Ría, a sub-system of the Bay of Ilha Grande, southeast Brazilian coast. Our results reveal the Carbon budget inside the Ría is not balanced by autotrophic production. Net community production is generally negative throughout the year, with a deficit ranging from 0.5 to 1.5 mg m-2 d-1 below what is necessary to sustain the local plankton ecosystem. We argue that the offset between daily primary production and heterotrophic Carbon consumption may be balanced by grazing of nano-heterotrophs on heterotrophic bacteria. Our conclusions apply to the majority of the Brazilian inner shelf waters outside of estuarine plumes and upwelling systems, thus with meso-oligotrophic conditions